Russian Orthodox Church and Nuclear Command and Control: A Hypothesis. (20th October 2019) - Adamsky, Dmitry (Dima)
Abstract: The Russian Orthodox Church plays an immense role in current Russian national security policy. The intertwining of the church and the strategic community is nowhere more visible than in the nuclear-weapons complex, where the priesthood has penetrated all levels of command, been involved in operational activities, and positioned itself as a provider of meanings for, and guardian of, the state's nuclear potential. The first work to highlight the phenomenon of the Russian church-nuclear nexus, this article focuses on the ecclesiastical impact on Russian nuclear command and control. The findings suggest that it is not inconceivable that the Russian military clergy—like the Soviet political officers and contrary to chaplains worldwide—might become future participants in decision making on matters of national security, and that de facto there might be two parallel chains of command authority emerging in Russia, with potential tensions between them. The article outlines the causes of this overlooked singularity and its implications for the theory and practice of international security.